Analisis Rute Pengiriman Kapal Peti Kemas Domestik Untuk Efisiensi Logistik Perusahaan Pelayaran Dengan Pendekatan Simulated Annealing (Studi Kasus Pt. XXX) - Putri, Kania Sekar Dinda; Herdian, Tedy; Febriansyah, Anton (Jurnal Sistem Transportasi & Logistik, 2024)
An abstract is a brief Route optimization and cargo optimization have a role in efforts to streamline the company's operational logistics activities. There are 5 routes on PT Temas Shipping, the results of the research are one route that dominates the least cargo, especially on the Sumatra route dominated by the skinny route or the least cargo. The method used is Traveling Salesman Problem (TSP) with Simulated Annealing (SA) approach. Based on the results of research based on MATLAB software, it can be found that the results of the comparison of the minimum optimization value between alternative ships and existing conditions, namely ship alternative 1 with a difference in the value of 10.16% (existing conditions ship 0. 117 tons and alternative ships 0.116 tons) in the existing condition of the ship, alternative ship 2 with a difference value of 406.56% (existing condition of the ship 0.7 tons and alternative ship 0.03 tons) in the existing condition of the ship In the existing condition of the ship. While testing the route using simulated annealing obtained the results of alternative route 1 with a smaller optimization value with a difference of 0.78% (Existing condition route of 1,424 Nm and Alternative route of 1,346 Nm) than the existing condition route..